Numerical analysis of corner-supported composite modular buildings under wind actions. (December 2021) - Peng, Jiahao; Hou, Chao; Shen, Luming
Abstract: This paper proposes a novel design of a corner-supported steel-concrete composite module that is suitable for multi-storey modular buildings. The strength and stiffness of the individual modules are improved through the designs of concrete-filled steel tubular (CFST) columns, laminated double beams, and integrated concrete slabs. The overall structural integrity of the modular buildings is improved through the designs of tenon-connected inter-module connections combined with beam-to-beam bolt connections. Analyses on modules reveal the effects of CFST columns on the failure mode and the lateral resistance of individual modules. Average increases of 21% in elastic stiffness and 33% in capacity under lateral loads are evident. The inter-module connections are proved to be effective in tying the modules together under lateral loads. A simplified FEA model is then developed for simulations of 12-storey modular buildings with various designs, of which the behaviours under wind actions are assessed according to the Australian Standards AS 1170.0–2. The drawbacks of the modular buildings are discussed, and the corresponding design recommendations are proposed. Graphical abstract: Unlabelled Image Highlights: A novel corner-supported composite module is proposed for multi-storey applications. The stiffness and strength of the module are improved by 21% and 33%, respectively. The proposed inter-module connections are sufficient in tying the connected modules. A 3-D FEA model is created for system-level analyses of the composite modular building. 12-storey modular buildings are potentially satisfactory under wind actions per AS 1170.